1994
DOI: 10.1063/1.112773
|View full text |Cite
|
Sign up to set email alerts
|

Insulating boundary layer and magnetic scattering in YBa2Cu3O7−δ /Ag interfaces over a contact resistivity range of 10−8–10−3 Ω cm2

Abstract: We have measured interface transport in thin-film YBa2Cu3O7−δ /Ag interfaces having resistivities ranging from 10−8 to 10−3 Ω cm2. Analysis of the interface I-V data indicates that tunneling is the predominant transport mechanism even for the in situ interfaces having contact resistivities of 1–7×10−8 Ω cm2. Zero-bias conductance peaks are also observed for the entire range of interface resistivity. The similarity of the zero-bias conductance peaks among these widely varying interfaces suggests that the low-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Even when the CRO is grown at different temperatures ͑600 and 700°C͒, we observe the same conductance-voltage characteristics, suggesting that the main interface property is probably not caused by cation diffusion. 8,11 However we do not observe a minimum in the zero bias conductance as a function of temperature as reported by Sanders et al 11 SrRuO 3 , which has the same structure as that of the CRO but a slightly bigger lattice constant, undergoes ferromagnetic ordering at temperatures around 150 K. 15 The magnetic ordering in SRO is believed to be a 4d itinerant ferromagnetism with a moment of about 1.1 B per Ru atom. In addition to the Kondo-assisted tunneling, leading to the zero bias peak, the conductance of the junction can also be modified at higher bias by resonant tunneling or hopping through localized states in the barrier.…”
Section: Conductance-voltage Characteristics Of Interfaces Betweensupporting
confidence: 60%
See 2 more Smart Citations
“…Even when the CRO is grown at different temperatures ͑600 and 700°C͒, we observe the same conductance-voltage characteristics, suggesting that the main interface property is probably not caused by cation diffusion. 8,11 However we do not observe a minimum in the zero bias conductance as a function of temperature as reported by Sanders et al 11 SrRuO 3 , which has the same structure as that of the CRO but a slightly bigger lattice constant, undergoes ferromagnetic ordering at temperatures around 150 K. 15 The magnetic ordering in SRO is believed to be a 4d itinerant ferromagnetism with a moment of about 1.1 B per Ru atom. In addition to the Kondo-assisted tunneling, leading to the zero bias peak, the conductance of the junction can also be modified at higher bias by resonant tunneling or hopping through localized states in the barrier.…”
Section: Conductance-voltage Characteristics Of Interfaces Betweensupporting
confidence: 60%
“…However this would be in contradiction with Sanders et al, 11 who reported a ZBCP for YBCO/Ag interface resistance varying from 10 Ϫ3 to 10 Ϫ8 ⍀ cm 2 and with Lesueur et al, 8 who observed the ZBCP in the ab direction YBCO/Pb junctions but not in the highly resistive c direction. It is not yet clear why only the YBCO/͑Ca,Sr͒RuO 3 interfaces show a ZBCP.…”
Section: Conductance-voltage Characteristics Of Interfaces Betweenmentioning
confidence: 67%
See 1 more Smart Citation
“…1 Near zero voltage bias, a peak is evident in the G-V curves of Fig. 1, which decreases with temperature and disappears for temperatures above ϳ30 K. 2,15 The zero-bias conductance peak is nearly independent of film manufacturer, junction resistivity ͑from 10 Ϫ8 ⍀ cm 2 to 10 Ϫ3 ⍀ cm 2 ͒, 15 and the counter-electrode material ͑including noble metals such as Au, Ag, and Pt, 16 metals having a high oxygen affinity, such as Pb, Ag, Cu, In, and Al, 1,2,15 as well as metallic oxides 17 ͒. Furthermore, oxygen annealing does not significantly alter the ZBCP even though the junction conductance changes by several orders of magnitude, as shown by the inset in Fig.…”
mentioning
confidence: 95%
“…The ZBCP that results from the Anderson-Appelbaum scattering has been studied thoroughly via previous experiments [18][19][20][21][22]. However, only until recently was there an alternate theory to explain the origin of the ZBCP.…”
Section: Introductionmentioning
confidence: 99%